Matching target dose to target organ [version 1; referees: 2 approved] - Desmond I. Bannon (F1000Research, 2016)
In vitro assays have become a mainstay of modern approaches to toxicology with the promise of replacing or reducing the number of in vivo tests required to establish benchmark doses, as well as increasing mechanistic understanding. However, matching target dose to target organ is an often overlooked aspect of in vitro assays, and the calibration of in vitro exposure against in vivo benchmark doses is often ignored, inadvertently or otherwise.  An example of this was recently published in Environmental Health Perspectives by Wagner et al., where neural stems cells were used to model the molecular toxicity of lead.  On closer examination of the in vitro work, the doses used in media reflected in vivo lead doses that would be at the highest end of lead toxicity, perhaps even lethal.  Here we discuss the doses used and suggest more realistic doses for future work with stem cells or other neuronal cell lines.